Strategi Pemberdayaan Desa Adat pada Era Globalisasi - I Nengah Suriata; I Wayan Antara (Public Inspiration : Jurnal Administrasi Publik, 2022)
As we know that the island of Bali is known as the Island of the Gods or the Island of a Thousand Temples. The majority of Balinese people are Hindus and they live in traditional village areas. Traditional villages in Bali have been heterogeneous from the start, when viewed in terms of caste/household, soroh or class. This heterogeneity is getting higher, due to the migration (migration) of non-Balinese ethnic groups to the Bali area. They carry customs, traditions, culture, religion, and other ethnic identities. With globalization, global culture can freely enter Bali. The existence of this condition certainly requires empowerment so that traditional villages still exist in the midst of the wave of globalization. The direction of empowerment is to develop the various capitals they have, without ignoring the normative principles that apply to the Unitary State of the Republic of Indonesia (NKRI), because Bali is part of the Republic of Indonesia. Likewise, global demands cannot be ignored, because Bali is part of the world. In this context, the principle of pluralism becomes very important for traditional villages in Bali.